Pengembangan Mersics.com sebagai E-diagnostic Assessment with Rasch Model pada Materi Prasyarat Bab Kinematika - Gunawan, Agun; Guntara, Yudi; Saefullah, Asep (JURNAL EKSAKTA PENDIDIKAN (JEP), 2024)
E-diagnostic Assessment is a diagnostic test instrument based on the Merscs.com website, which is used to determine students' initial level of understanding before carrying out physics learning. This research aims to determine the validity and reliability of the development of Mersics.com as an e-diagnostic assessment of the prerequisite material for the kinematics chapter. The limited trial subjects in this research were 75 class XI MIA students. Validity analysis uses the Item Response Theory (IRT) approach with one Logistic Parameter (PL), the difficulty level parameter, better known as the Rasch Model. The research results showed that 56 questions were declared valid by experts using Content Validity Ratio (CVR > 0) analysis. Meanwhile, the results of the analysis based on the Rasch Model showed 20 valid questions in the Understanding of Motion sub-chapter, nine valid questions and one invalid question item in the GLB and GLBB sub-chapters, ten valid questions in the Parabolic Motion sub-chapter, nine valid questions and one the question item is invalid and in the Circular Motion sub-chapter. The reliability of the questions as a whole is declared reliable. It can be concluded that this E-diagnostic Assessment is suitable for use in physics learning.